Trauma and psychosis new directions for theory and therapy - Larkin, Warren; Morrison, Anthony P. (Routledge, Taylor & Francis Group, 2006)
Provides an understanding of the possible relationships between the experience of trauma and the range of phenomena referred to as psychosis. This work brings together contributions from leading clinicians and researchers in a range of fields including clinical psychology, mental health nursing and psychiatry.